Pancreatic Extracts for Painful Chronic Pancreatitis: Micronutrient Antioxidant Therapy by Proxy - Braganza, Joan M (JOP. Journal of the Pancreas, 2014)
No abstract available Image: Stopford Building. The University of Manchester's Medical School, built 1969-72 to the designs of Harry S. Fairhurst & Son. (From http://www.geograph.org.uk - © Copyright Stephen Richards)